S = ⌊ 1 ⌋ + ⌊ 2 ⌋ + ⌊ 3 ⌋ + ⋯ + ⌊ 1 9 8 8 ⌋
Find the value of S .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Used the same method.
why sum(n(2n+1)) ?
Same method...
Really nicely done!
⌊ 1 9 8 8 ⌋ = 4 4 4 4 2 = 1 9 3 6 1 9 8 8 − 1 9 3 5 = 5 3 5 3 × 4 4 = 2 3 3 2 There are 2 n + 1 numbers that takes the value n. So S = 2 3 3 2 + n = 1 ∑ 4 3 n ( 2 n + 1 ) S = 2 3 3 2 + n = 1 ∑ 4 3 ( 2 n 2 + n ) S = 2 3 3 2 + n = 1 ∑ 4 3 2 n 2 + n = 1 ∑ 4 3 n S = 2 3 3 2 + 3 4 3 × 4 4 × 8 7 + 2 4 3 × 4 4 S = 2 3 3 2 + 5 4 8 6 8 + 9 4 6 S = 5 8 1 4 6
Same here :)
Log in to reply
sir can you please tell how would the same question be done if we would be given the sum of these roots and we would be asked to find the last term of the root which is 1988 in this case
Log in to reply
I understood your question like this: If you were given the final value the how would you compute the last term? Well, one way is to trace back through the steps Find the largest number which is less than the given value S and it must be the largest number ( m ,say.) which can be written as sum of squares up to some n . Now you can compute n 2 and the difference between S and m will be divisible by n + 1 . The quotient obtained can be added to n 2 . You have the answer!!!
The series, S , shows an apparent pattern. In approaching the problem, what must be done first is to find the greatest perfect square integer < 1 9 8 8 . 1 9 8 8 is an integer ∈ [ 4 4 2 , 4 5 2 ] , so it is obvious that we are to choose 4 4 2 because 1 9 3 6 < 1 9 8 8 . Now that we have chosen our upper bound of summation, we proceed to the establishment of our sum. So we would have ( 4 4 × 5 3 ) + i = 1 ∑ 4 3 ( n ( 2 n + 1 ) ) = 2 3 3 2 + i = 1 ∑ 4 3 ( 2 n 2 + n ) = 2 3 3 2 + 2 × i = 1 ∑ 4 3 n 2 + i = 1 ∑ 4 3 n . At this point, we will use the formula for the sum of the squares of the first n natural numbers and for the sum of the first n natural numbers: S n s q u a r e d = 6 [ n ( n + 1 ) ( 2 n + 1 ) ] ; S n = 2 [ n ( n + 1 ) ] , respectively. By plugging in n = 4 3 , we yield 2 3 3 2 + 2 [ 6 ( 4 3 ) ( 4 3 + 1 ) ( 2 ( 4 3 ) + 1 ) ] + 2 ( 4 3 ) ( 4 3 + 1 ) which simplifies to 2 3 3 2 + ( 4 3 × 4 4 × 2 9 ) + ( 4 3 × 2 2 ) = 5 8 1 4 6 . ∴ S = ⌊ 1 ⌋ + ⌊ 2 ⌋ + ⌊ 3 ⌋ + . . . + ⌊ 1 9 8 8 ⌋ = 5 8 1 4 6
Problem Loading...
Note Loading...
Set Loading...
We can notice that,
m values ⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ ⌊ n 2 ⌋ ⌊ n 2 + 1 ⌋ … ⌊ ( n + 1 ) 2 − 1 ⌋ = n = n = n m = ( n + 1 ) 2 − 1 − n 2 + 1 = 2 n + 1
And also see that, 4 4 2 = 1 9 3 6 < 1 9 8 8 < 2 0 2 5 = 4 5 2
Therefore, S can be written as,
S = 1 ≤ n ≤ 4 3 ∑ n ( 2 n + 1 ) + 4 4 ( 5 3 ) = 1 ≤ n ≤ 4 3 ∑ ( 2 n 2 + n ) + 2 3 3 2 = 2 1 ≤ n ≤ 4 3 ∑ n 2 + 1 ≤ n ≤ 4 3 ∑ n + 2 3 3 2 = 2 ⋅ 6 ( 4 3 ) ( 4 4 ) ( 8 7 ) + 2 ( 4 3 ) ( 4 4 ) + 2 3 3 2 = 5 8 1 4 6